Correlation of quality of life and severity in patients with melasma - Aryal, Eliz; Khadka, Anupa; Bhattarai, Sabeena (Journal of Kathmandu Medical College, 2022)
Background: Melasma is a disorder of acquired facial hyperpigmentation, typically affecting young females. It is known to cause a great psychological impact and a significant negative effect on a patient’s quality of life. Objectives: To explore the correlation between the quality of life in melasma patients and the severity of melasma. Methods: This hospital-based, analytical, cross-sectional study was conducted from 2020 October to 2021 December in the Department of Dermatology, Venereology and Leprology of Kathmandu Medical College after institutional ethical clearance, in 101 patients recruited by convenience sampling. The quality of life was calculated using the Nepali version of the Dermatology Life Quality Index (DLQI) questionnaire and severity of melasma was calculated using modified Melasma Area and Severity Index (mMASI). Data analysis was done by SPSS v.24. Results: The study included 101 patients of melasma with a young female preponderance. Seventy-eight (75.7%) being female and 43 (42.6%) being between the age of 21-30 years. The mean DLQI score was 10.39 ± 3.22; interpreted as having a ‘very large effect on a patient’s life.’ While the mean mMASI score was calculated to be 5.53 ± 2.69; interpreted as a melasma severity score (MSS) of ‘moderate severity.’ A significant positive moderate correlation r = 0.431 (p <0.001) was observed between mMASI and DLQI. Conclusion: Melasma is a common pigmentary disorder that has a very large effect on the patient’s quality of life and this correlates directly with the severity of melasma.